Reexpansion pulmonary edema in children - Rodrigues,Antonio Lucas L. (2013)
OBJECTIVE To present a case of a patient with clinical and radiological features of reexpansion pulmonary edema, a rare and potentially fatal disease. CASE DESCRIPTION An 11-year-old boy presenting fever, clinical signs and radiological features of large pleural effusion initially treated as a parapneumonic process. Due to clinical deterioration he underwent tube thoracostomy, with evacuation of 3,000 mL of fluid; he shortly presented acute respiratory insufficiency and needed mechanical ventilation. He had an atypical evolution (extubated twice with no satisfactory response). Computerized tomography findings matched those of reexpansion edema. He recovered satisfactorily after intensive care, and pleural tuberculosis was diagnosed afterwards. COMMENTS Despite its rareness in the pediatric population (only five case reports gathered), the knowledge of this pathology and its prevention is very important, due to high mortality rates. It is recommended, among other measures, slow evacuation of the pleural effusion, not removing more than 1,500 mL of fluid at once.